Atsar Istikhdam al-Wasail al-Ta'limiyyah fi Ta'lim al-Lughah al-'Arabiyyah fi Jami'ah Indonesiya al-Tarbawiyyah bi Jazirah Jawa al-Gharbiyyah - Nasrullah, Yufi Mohammad (Universitas Islam Negeri Raden Intan Lampung, 2017)
Abstract : This study aimis to: Obtain acquaintance with the importance of Teaching Aids (T.A), and its role in teaching process; To get acquaintance with the problems that confront the using of Teaching Aids (T.A), in teaching Arabic language in Indonesia University of Education; Rising the qualification of the teachers, in employing the Teaching Aids (T.A), in teaching Arabic language; To achieve a futuristic view, that can be reflected in the Teaching Aids (T.A) program, of teaching Arabic language in Indonesia University of Education.The most important of these result are: Using the Teaching Aids (T.A), in teaching Arabic language, has a big role to make the teaching useful for non- Arabic language speakers, where as: (1) It makes the teacher to be an investigator and an executor, instead of to be a commentator and a narrator. (2) It assists to present, perform, control and verify the course in the education situation, as it saves time and sacrificed effort. (3) It brings up students motivation, and encourages them to interact and participate in the lesson, as it develops curiosity by the students. The course which includes Teaching Aids (T.A) will be exiting and understood. It is, no doubt, essential to prepare the teacher of Arabic language for non-native speakers, a professional prepare, according to the designing and using of the Teaching Aids, and drills him to use educational instruments, in order to be accompanying with the technology and the modern demands, and helpful to realize the desired aims.The existence of advanced Teaching Aids (T.A), and using it with suitable way in teaching Arabic language, will assist the teacher to arrive at the required goals in teaching Arabic language. Keywords : Teaching aids, and Teaching Arabic language.